A guidebook for city and county managers : meeting today's challenges - Bourey, James M. (New York, NY ; Abingdon, Oxon : Routledge, Taylor & Francis Group, 2022)
Whether you are a student preparing for a career in public administration, mid-career professional manager or seasoned veteran, A Guidebook for City and County Managers provides policy guidance and advice to local governmental challenges and issues. Assuming a knowledge of the basics of public management, James M. Bourey provides real world recommendations for issues managers are facing this decade and beyond. Relying on experience from his long career in local government in chief executive positions in city, county and regional council management in locations throughout the US, Bourey outlines the best approaches to the most critical issues for local governments. The book is comprehensive in its breadth of subject matter yet targeted in the recommendations which focus on the most critical issues. Social equity, environmental protection and global warming, good fiscal management, adequate public infrastructure and active citizen engagement are important themes throughout. Merely being an administrative caretaker is not sufficient; managers must have the knowledge of ways to improve their communities and take the initiative to enhance the quality of life of its residents. Making a difference is both the reason for the job and its reward. This book helps to provide a roadmap for the journey.
Introduction 1. Social Justice 2. Local Government Finance 3. Land Use Planning and Regulation 4. Environmental Stewardship 5. Housing 6. Transportation 7. Public Facilities/Infrastructure 8. Economic Development 9. Education 10. Health Care 11. Intergovernmental Relations 12. Technology 13. Public Engagement 14. Conclusion
OCLC-licensed vendor bibliographic record.
Keywords: Municipal government by city manager -- United States; City managers -- United States; County manager government -- United States; Local government -- United States; Public administration -- United States; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Government / Local